Anesthesia for peroral endoscopic myotomy: A retrospective case series - Nithin Jayan; Jaya Susan Jacob; Mohan Mathew; Roy Joy Mukkada (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Peroral endoscopic myotomy (POEM) is a safe and minimally invasive modality regarded as the first-line management of all types of achalasia. POEM is performed under general anesthesia with endotracheal intubation using an orally inserted flexible fiberscope. The aim of this study is to describe the anesthetic management of POEM for achalasia. Material and Methods: A chart review of 21 patients who underwent POEM for achalasia at our center from March 2013 to June 2015 was performed. Results: In the 21 patients, the end-tidal carbon dioxide was elevated following esophageal carbon dioxide insufflation and required adjustments in ventilation. POEM was successfully completed, and the patients were extubated immediately afterward. Subcutaneous emphysema occurred in five patients. Complications such as mediastinitis, pleural effusion, pneumoperitoneum, and pneumomediastinum were managed conservatively. Esophageal perforation occurred in one patient and needed surgical intervention. Conclusion: For patients with achalasia, POEM offers the efficacy of surgery with the lower cost and morbidity of an endoscopic procedure. Prevention of aspiration and carbon dioxide insufflation-related complications are the two aspects that demand vigilance from the anesthesiologist.